Direct observation of NiSi lateral growth at the epitaxial θ-Ni2Si/Si(1 0 0) interface. (15th October 2015) - El Kousseifi, M.; Hoummada, K.; Epicier, T.; Mangelinck, D.
Graphical abstract: Abstract: The first stages of NiSi phase formation at the expense of θ -Ni2 Si and a Si substrate are investigated by transmission electron microscopy (TEM). These measurements show the presence of a low density of NiSi particles at the θ -Ni2 Si/Si(1 0 0) interface and allow their complete shape to be determined. This stage corresponds to the lateral growth of NiSi at the epitaxial θ -Ni2 Si/Si(1 0 0) interface. The shape of these particles is in agreement with the predicted models, and the shapes were fitted by an analytical expression derived from the model developed by Klinger et al.